EXPERIMENTAL INVESTIGATION OF COTTON DUST INFLUENCE ON POWER OUTPUT OF PHOTOVOLTAIC MODULE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This research presents the influence of cotton dust on photovoltaic (PV) systems installed in textile industries. An indigenously designed experimental setup is installed, and two different experiments have been conducted based on cotton dust concentrations from (28000 – 52431) mg/cm2 in twelve days. The results showed that the output of the PV module decreased drastically as the cotton dust accumulation increased. The accumulated cotton dust samples are collected from the PV surface for physical examination. It is observed that cotton dust has a unique stickiness, which causes the fibre to adhere to the PV module surface. When exposed to sunlight for an extended period, its color becomes dull, and yellowness increases, which decreases the transmittance and forms large agglomerates due to an increase in humidity, which blocks irradiance. The results of this research can be utilized to devise a specific cleaning mechanism for the textile sector that will increase the PV output.
Keywords: Cotton dust; Photovoltaic (PV) module; Renewable energy; Textile industry; Power loss